2006
DOI: 10.1074/jbc.m604025200
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Neuronal Morphology by Toca-1, an F-BAR/EFC Protein That Induces Plasma Membrane Invagination

Abstract: Actin reorganization is important for regulation of neuronal morphology. Neural Wiskott-Aldrich syndrome protein (N-WASP) is an important regulator of actin polymerization and also known to be strongly expressed in brain. Recently, Toca-1 (transducer of Cdc42-dependent actin assembly) has been shown to be required for Cdc42 to activate N-WASP from biochemical experiments. Toca-1 has three functional domains: an F-BAR/EFC domain at the N terminus, an HR1 at the center, and an SH3 domain at the C terminus. The F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
62
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(69 citation statements)
references
References 22 publications
5
62
2
Order By: Relevance
“…Second, the increased axonal branching observed upon syndapin I RNAi is consistent with similar aberrant axon branching upon Arp3 and N-WASP knockdown. The comparative data we collected for N-WASP RNAi are hereby in line with a previous report (Kakimoto et al, 2006). Also in the study of Kakimoto et al (2006), N-WASP deficiency was found to impair proper axon development.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…Second, the increased axonal branching observed upon syndapin I RNAi is consistent with similar aberrant axon branching upon Arp3 and N-WASP knockdown. The comparative data we collected for N-WASP RNAi are hereby in line with a previous report (Kakimoto et al, 2006). Also in the study of Kakimoto et al (2006), N-WASP deficiency was found to impair proper axon development.…”
Section: Discussionsupporting
confidence: 74%
“…The comparative data we collected for N-WASP RNAi are hereby in line with a previous report (Kakimoto et al, 2006). Also in the study of Kakimoto et al (2006), N-WASP deficiency was found to impair proper axon development. Our loss-of-function data show that likewise syndapins play a crucial role in axon development.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…In support of this hypothesis, depletion of the actin nucleator Arp2/3 or WAVE leads to the loss of one to two GABA neurons at 25°, suggesting a weak P-cell nuclear migration defect (Xiong et al 2011). A third possibility is that TOCA-1 is functioning through its known roles in membrane tubulation and clathrin-mediated endocytosis (Ho et al 2004;Kakimoto et al 2006;Bu et al 2009Bu et al , 2010Fricke et al 2009;Giuliani et al 2009). In Drosophila, Rab-mediated endocytosis and vesicular transport contribute to nuclear positioning in the developing eye (Houalla et al 2010).…”
Section: Discussionmentioning
confidence: 73%